A Factorial Study on the Design and Evaluation of Carbamazepine Floating Tablets Employing Starch-Urea-Borate - Chowdary, K.P.R.; Santosh Kumar, R. (Asian Journal of Chemistry, 2010)
The objective of the study is to design and evaluate carbamazepine floating tablets employing starch-urea-borate, a modified starch based polymer to enhance its oral bioavailability and to achieve controlled release of carbamazepine. The individual and combined effects of sodium bicarbonate (gas generating agent), bees wax (hydrophobic floating agent) and ethyl cellulose (floating enhancer) on floating time and drug release were also investigated in a 23-factorial study. Starch-urea-borate is an efficient matrix former for floating tablets based on gas generation principle. Drug release from the prepared tablets was slow and spread over more than 24 h and depended on the composition of the matrix i.e., concentration of sodium bicarbonate, bees wax and ethyl cellulose. Carbamazepine release was diffusion controlled and followed zero order kinetics. Non-fickian diffusion was the drug release mechanism from the prepared floating tablets. The individual and combined effects of sodium bicarbonate, bees wax and ethyl cellulose on the floating time and drug release were significant (p < 0.05). Floating tablets formulated employing sodium bicarbonate (10 %), ethyl cellulose (10 %) and bees wax (20 %) and starch-urea borate as matrix former exhibited in vitro buoyancy over 43 h and good controlled release over more than 24 h and were found suitable for once-a-day administration.